The Ecumenical Significance of the Holy and Great Council of the Orthodox Church (The ecumenical review, 2017)
From 20 to 26 June 2016, following a century of preparatory work, the Holy and Great Council of the Orthodox Church met on the island of Crete. Among the various documents agreed by the council, the most controversial before, during, and after the council was the one on The Relations of the Orthodox Church with the Rest of the Christian World. This article sets out the importance of this statement, and considers and responds to the various criticisms of it that have emerged among certain Orthodox groups and individuals. The article concludes that despite such objections, the statement has a crucial ecumenical significance, and that, for the first time in its history, the Orthodox Church has taken a conciliar decision with regard to participation in the ecumenical movement and engagement in theological dialogue with other Christian churches and confessions.